Foreword (to Sumer 18) - Bāqir, Ṭaha
Aqar Quf and Tell Harmal; Hatra; Samarra and al-Ukhaidir; al-Ukhaidir: its Dating Re-examined and Clarified; Excavations; Tell Dhiba’i: New Mathematical Texts (with copy, transcription), Translation, Notes and Mathematical Commentary.